Two ‘Performances’ by Magaly Solier: Building a Cultural Image - Bedoya, Ricardo (2016)
This article analyzes two public appearances of the actress and singer Magaly Solier, early in her career: the Berlinale 2009 Award Ceremony, where the film La teta asustada obtained the most important award; and the interview given to a Peruvian blog while visiting the “Yuyanapaq” photo exhibit. Both are interpreted as the construction of a personal narrative: a young woman, inheritor of the memory of violence caused by the internal armed conflict, who becomes a mediator between her tradition and mass media. The text summarizes chapter four of the thesis entitled “Made in Huanta. Transits and scenarios of Magaly Solier: the construction of a cultural text” (Pontificia Universidad Católica del Perú, August 2012).